Recent advances in transition metal nitrides for hydrogen electrocatalysis in alkaline media: From catalyst design to application - Tang, Siyuan; Zhang, Zhipeng; Xiang, Jun; Yang, Xinchun; Shen, Xiangqian; Song, Fuzhan (Frontiers in Chemistry, 2022)
With the increase of population as well as energy demand, hydrogen (H2) is considered as a clean candidate that can replace fossil fuel to meet future energy demand. Although platinum group metal (PGM) catalysts have excellent performance, their scarcity and high cost limit the industrial application. Therefore, it is necessary to develop low-cost and efficient non-PGM catalysts. Transition metal nitrides (TMNs) have attracted much attention because of their excellent hydrogen electrochemistry, including hydrogen evolution reaction (HER)/hydrogen oxidation reaction (HOR) performance. In this paper, we first review and discuss the mechanism of HER/HOR in alkaline media. Based on these understanding, we compare and evaluate electrocatalytic performance for the HER/HOR TMNs catalysts recently reported. Finally, we look forward to the sustainable and clean hydrogen energy devices and prospects and research trends.